What influences success of high school students: a phenomenological perspective - Raterink, George V., author; Porter, Charles F., advisor; Banning, James H., committee member; Paccione, Angela V., committee member; Kennedy, Cathy, committee member (Colorado State University. Libraries, 2001)
The concept of how students achieve success in high school is a difficult one. The researcher assumed that student success was affected by both internal and external forces. The purpose of this qualitative study was to discover what those forces were and how faculty, parents and administrators might assist high school students. Research included a brief history of the small rural community. Assumptions were made by the researcher about possible affects on student success that included but were not limited to peers, family, school faculty, and the culture of the education in the community. After nominations by the high school's accountability committee, five successful participants were selected to be involved in the focus group. During the focus group five questions were asked. The focus group was taped; field notes were taken, and later transcribed. The focus group identified three skills needed for success in high school: (a) technical skills, (b) communication skills, and (c) personality skills. Four commonalties were also identified by the focus group as significant for success: (a) influence of a significant person, (b) experiencing failure, (c) having a leadership role, and (d) involvement in extracurricular activities. Focus group answers were used to develop further questions for the individual interviews with each of the same participants. The interviews were taped, notes were taken, and transcriptions were made. The individual interviews determined nine attributes that students perceived that were important to their success: (1) self-responsibility, (2) self-starter, (3) self-confident, (4) street-smart, (5) quick-thinker, (6) flexible and adaptable, (7) risk-taker, (8) change-agent, and (9) life long learner. I followed the interviews with phone calls to gain further reliability of the information gathered. From the focus group and the individual interviews three central themes emerged. Successful students are happy. Successful students are goal oriented because they tend to mentally mature earlier. A third theme is successful students are not afraid of failure and have the resiliency to bounce back after failure. It appears that internal influences such as one's own motivation and maturity are more significant to success than external influences. Based on the findings, the following recommendations were made. School districts should promote several initiatives to help students succeed including: 1. Greater faculty involvement with students and parents. 2. Comprehensive counseling programs for students, parents, and faculty. 3. More parent involvement in academic and extracurricular activities for students. 4. A board of education strategic plan focused on the three central themes, pursuit of happiness, goal oriented, and resiliency. Further study should be done on both successful and unsuccessful students. A study should also be done of students who are moving through the school system, before they reach high school.
Keywords: educational psychology; secondary education